Interleukin-1 beta promotes epithelial-mesenchymal transition and a stem cell phenotype of colon cancer cells via Zeb1/2 - Li, Yijing (Kansas State University, 2012)
Interleukin-1 beta (IL-1β) is an important mediator of inflammatory response, and the elevated expression of IL-1β is correlated with tumor growth and metastasis. Epithelial-mesenchymal transition (EMT) is a reversible transition between epithelial phenotype and mesenchymal phenotype. Usually, EMT can be identified by its unique morphology change and expression of EMT markers. In our study, we have found after treated HCT-116, a colon cancer cell line, and human primary colon cancer cells with IL-1β, cells began to display mesenchymal phenotype with highly down-regulated E-cadherin expression and up-regulated ZEB factors expression. For colon cancer cells, sphere formation assay in serum free medium (SFM) with the presence of growth factors is used to identify cancer stem cell population. We have shown that IL-1β can induce colon cancer stem cell proliferation and express stem cell markers (Bmi1, Nanog, and Nestin). In addition, besides the stem cell markers, we also found ZEB factors were highly up-regulated in spheroid cells as well. We silenced Zeb1 expression and investigated the effect of IL-1β on shZeb1 HCT-116 cells. The results indicated Zeb1 knockdown not only inhibited IL-1β-induced EMT but also reduced proliferation of spheroid cells and inhibited Bmi1 expression. Therefore, ZEB factors must play an important role in both EMT process and cancer stem cell development. From our data, we conclude that IL-1β promotes epithelial-mesenchymal transition and a stem cell phenotype in colon cancer via ZEB factors.
Keywords: Interleukin-1 beta; colon cancer; Biology (0306); Veterinary Medicine (0778)